Cultural variables determining well-being of the population above the age of sixty - Szymańska, Jolanta; Pietryka-Michałowska, Elżbieta; Toruń-Jurkowska, Anna (Polish Journal of Public Health, 2010)
Introduction. The progressing ageing process and consequently deteriorating health status change the attitudes of man towards life in all its aspects: heath, family, professional and social life. Therefore, health status is assessed not only with biomedical indices but also with subjective feelings concerning health based on personal experiences and reflections about what we feel and who we are. Aim. The key objective of the present study was to determine whether and to what extent the socio-economic status and lifestyle affected the subjective assessment of health in the population above the age of 60. Material and methods. The study population included 176 individuals aged 60-90 years getting primary health care services. The questionnaire designed by the authors was distributed amongst patients having appointments with their family doctor between January and December 2007. Conclusion. The questionnaire results were statistically analysed and the following conclusions were arrived at: self-assessment of health is a total judgment of effects of many subjective and objective health indices perceived by an individual. Self-assessment and satisfaction with health status of the elderly are more dependent on their functional efficiency than the presence of chronic diseases